PENGARUH DER, ROA, ROE TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pratama, Heru Andika; Afriyeni, Afriyeni (Creative Research Management Journal, 2022)
This study aims to examine the effect of DER, ROA, ROE on stock prices. The sampling technique is a total sampling method in which the entire population is sampled. The research sample is a banking company listed on the Indonesia Stock Exchange (IDX). Where the companies listed on the IDX during the last period, namely 2021, consisted of 44 companies, with a total final sample of 44 companies during the 5 year research period. Data was collected by documentation and literature study methods. Data analysis techniques using the Classical Assumption Test and Hypothesis Testing using panel data regression using Eviews 9. The research findings show that: (1) DER has a significant effect on stock prices, (2) ROA has a significant effect on stock prices, (3) ROE has a significant effect on stock prices